A combined experimental–numerical approach for permeability characterization of engineering textiles. Issue 7 (3rd May 2021) - Schmidt, Tim; May, David; Duhovic, Miro; Widera, Aaron; Hümbert, Martina; Mitschang, Peter
Abstract: Extensive experimental test programs are required for the characterization of textile permeability, which is essential for the design of liquid composite molding processes. In this study, an experimental–numerical approach is presented, aiming to partially substitute experiments by numerical simulations. This approach uses 3D microscale simulations to evaluate the permeability within rovings and attribute these values to statistical volume elements of the textile at the mesoscale. To further improve accuracy, a calibration method has been defined. In order to validate the functionality of this approach the permeability of a glass fiber woven and a non‐crimp fabric at fiber volume contents (FVCs) between 50 and 60% were predicted. For the non‐calibrated but virtually compacted models with FVCs of 55 and 60%, the deviation ranges from −27% to +42%. This seems acceptable considering the typical scatter in experimental tests, for example, a CV of 20–50% was measured in recent permeability benchmarks. The numerically determined permeability was then used as input for numerical filling simulations at part level (macroscale). The resulting filling times were then compared to results of simulations based on experimental input values. Abstract :